Impact of Critical Illness on Resource Utilization: A Comparison of Use in the Year Before and After ICU Admission*. Issue 11 (November 2019) - Hirshberg, Eliotte L.; Wilson, Emily L.; Stanfield, Valoree; Kuttler, Kathryn G.; Majercik, Sarah; Beesley, Sarah J.; Orme, James; Hopkins, Ramona O.; Brown, Samuel M.
Abstract : Objectives: Increasingly, patients admitted to an ICU survive to hospital discharge; many with ongoing medical needs. The full impact of an ICU admission on an individual's resource utilization and survivorship trajectory in the United States is not clear. We sought to compare healthcare utilization among ICU survivors in each year surrounding an ICU admission. Design: Retrospective cohort of patients admitted to an ICU during one calendar year (2012) in a multipayer healthcare system. We assessed mortality, hospital readmissions (categorized by ambulatory care sensitive conditions and emergency department), and outpatient visits. We compared the proportion of patients with visits during the pre-ICU year versus the post-ICU year. Patients: People admitted to an Intermountain healthcare ICU for greater than 48 hours in the year 2012 Interventions: None. Measurements and Main Results: Among 4, 074 ICU survivors, 45% had increased resource utilization. Readmission rates at 30-day, 90-day, and 1-year were 15%, 26%, and 43%. The proportion of patients with a hospital admission increased significantly in the post-ICU period (43% vs 29%; p < 0.001). Of patients with a readmission in the post-ICU period, 24% were ambulatory care sensitive condition. Patients with increased utilization differed by socioeconomic status, insurance type, and severity of illness. Sixteen percent of patients had either an emergency department or inpatient admission, but no outpatient visits during the post-ICU period. Conclusions: An ICU admission is associated with increased resource utilization including hospital readmissions, with many due to an ambulatory care sensitive condition. Lower socioeconomic status and higher severity of illness are associated with increased resource utilization. After an ICU visit patients seem to use hospital resources over outpatient resources. Interventions to improve and coordinate care after ICU discharge are needed. Abstract : Supplemental Digital Content is available in the text.